Verbs (a book of fimiliar verbs) - Yaseen, ghulam (Nawab sons publication; Rawalpindi)
"Verbs: A Book of Familiar Verbs" is an educational resource that introduces and explains commonly used verbs, helping readers to understand their meanings and proper usage in everyday language.